Systematic Review: The Effect of Using Virtual Laboratory On Physics Learning to Improve Student’s Concept Understanding - Annisa Rahmi; Hidayati Hidayati; Hufri H; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2023)
The 2013 curriculum requires teachers to be skilled in the learning process which makes students more active in learning activities. Physics learning does not only discuss theory, but also needs to do practical work so that students understand the concepts being taught, if schools have limitations regarding laboratory equipment, then they can use virtual laboratories instead. There are many research articles about the use of virtual laboratories in physics learning. However, there has been no systematic study that summarizes these studies, for this reason a systematic study is needed that will produce new information. This study aims to: (1) analyze the model/strategy/method of using virtual laboratories in learning physics, (2) analyze the effect of virtual laboratories in learning physics on increasing students' understanding of concepts. The method used in this study is a systematic review. The collected articles totaled 25 articles published in the last 10 years in national and international journals. Data analysis was performed using predetermined instruments and effect size formulas. The results of the study are learning models/learning strategies/learning methods for using virtual laboratories in physics learning to improve students' understanding of concepts, there are 7 learning models, and 2 learning approaches. The discovery learning learning model and inquiry learning model are the most widely used. momentum and impulse materials have a good effect on students' understanding of concepts. with an average effect size value of 1.95 with a high influence category